RETRACTED: Measurement and analysis of Chinese journal discriminative capacity. Issue 1 (February 2020) - Zhang, Baolong; Wang, Hao; Deng, Sanhong; Su, Xinning
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been retracted upon request of the authors. After publication of this article, the authors contacted the Editor-in-Chief to alert her of errors in the data used in the study. The bibliographic data contains several journal mismatches which lead to the deviation of the data results, as well as the errors in the figures and tables in the paper. After careful consideration, the authors have requested to retract and the Editor-in-Chief has agreed. The authors offer their apologies to readers, Editors and reviewers of this paper.